2016
DOI: 10.1002/wrna.1359
|View full text |Cite
|
Sign up to set email alerts
|

Function and evolution of the long noncoding RNA circuitry orchestrating X‐chromosome inactivation in mammals

Abstract: X-chromosome inactivation (XCI) is a chromosome-wide regulatory process that ensures dosage compensation for X-linked genes in Theria. XCI is established during early embryogenesis and is developmentally regulated. Different XCI strategies exist in mammalian infraclasses and the regulation of this process varies also among closely related species. In Eutheria, initiation of XCI is orchestrated by a cis-acting locus, the X-inactivation center (Xic), which is particularly enriched in genes producing long noncodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 144 publications
(319 reference statements)
0
45
0
1
Order By: Relevance
“…Murine XCI consists of a series of events orchestrated by a single locus, known as the X Inactivation Center (XIC). Chronologically, it was demonstrated that the murine XIC and chromosome interactions at XIC count the number of X chromosomes (15), select the X chromosome to be inactivated (X i )(14, 16), propagate stable heterochromatin on the X i (1719), and direct the localization of the stable X i heterochromatin to the lamina (20). These complex events are orchestrated by the XIC through the actions and interactions of multiple long non-coding RNAs, proteins, and functional elements encoded therein.…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
See 4 more Smart Citations
“…Murine XCI consists of a series of events orchestrated by a single locus, known as the X Inactivation Center (XIC). Chronologically, it was demonstrated that the murine XIC and chromosome interactions at XIC count the number of X chromosomes (15), select the X chromosome to be inactivated (X i )(14, 16), propagate stable heterochromatin on the X i (1719), and direct the localization of the stable X i heterochromatin to the lamina (20). These complex events are orchestrated by the XIC through the actions and interactions of multiple long non-coding RNAs, proteins, and functional elements encoded therein.…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
“…There are two chromatin domains, known as Topologically Associated Domains, or TADs, that comprise the XIC. These TADs are thought to have directly opposing functions, which are mediated by the distinct genomic elements present in each; the Tsix TAD mediates XCI repression, and the Xist TAD mediates XCI progression(17). …”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
See 3 more Smart Citations